2022
DOI: 10.3390/ijms232314971
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Spectrum of Familial Hypercholesterolaemia in the Malaysian Community: Identification of Pathogenic Gene Variants Using Targeted Next-Generation Sequencing

Abstract: Familial hypercholesterolaemia (FH) is caused by mutations in lipid metabolism genes, predominantly in low-density lipoprotein receptor (LDLR), apolipoprotein B (APOB), proprotein convertase subtilisin/kexin-type 9 (PCSK9) and LDL receptor adaptor protein 1 (LDLRAP1). The prevalence of genetically confirmed FH and the detection rate of pathogenic variants (PV) amongst clinically diagnosed patients is not well established. Targeted next-generation sequencing of LDLR, APOB, PCSK9 and LDLRAP1 was performed on 372… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 104 publications
1
7
0
Order By: Relevance
“…This variant is located at the second disulphide-rich repeat in the receptor protein binding domain and impacts the processing and intracellular transport of the generated protein ( 27 ). Moreover, some studies have suggested a damaging outcome of this variant ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…This variant is located at the second disulphide-rich repeat in the receptor protein binding domain and impacts the processing and intracellular transport of the generated protein ( 27 ). Moreover, some studies have suggested a damaging outcome of this variant ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCSK9 variants, E498A and R499G were discovered by the study of Razman et al, (2022). Both novel variants were identified among 35 clinically diagnosed Malaysian FH patients and classified as likely pathogenic according to ACMG guidelines (Richards et al, 2015).…”
Section: Modeling Of the Pcsk9 Variantsmentioning
confidence: 99%
“…In this work, we employed molecular dynamics (MD) simulations to examine the dynamics of LDLR structure while interacting with PCSK9. Additionally, we investigated the impact of two novel PCSK9 variants, E498A and R499G, found in Malaysia FH patients (Razman et al, 2022) on the LDLR-PCSK9 complex and their interactions. The simulations captured the behavior and conformational changes of the LDLR structure while interacting with PCSK9.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis showed that the pooled prevalence of HeFH based on genetic testing or established clinical diagnostic criteria among the general adult population was 1 in 303 [ 14 ]. In Malaysia, the prevalence of clinically diagnosed HeFH was estimated to be 1 in 100 [ 15 ], while the prevalence of genetically confirmed HeFH was recently reported as 1 in 427 [ 16 ]. This is comparable to the prevalence in other countries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%